2008
DOI: 10.1002/mus.21096
|View full text |Cite
|
Sign up to set email alerts
|

Staircase but not posttetanic potentiation in rat muscle after spinal cord hemisection

Abstract: Spinal cord hemisection (SCH) results in atrophy of skeletal muscle and altered contractile properties. In this study our purpose was to assess staircase and posttetanic potentiation in the rat gastrocnemius muscle in situ, 1 week after SCH. Tetanic force was reduced by SCH, but twitch amplitude was not. The time course and magnitude of staircase during stimulation at 5 HZ (for 21 s) was similar in the control, sham-operated, and SCH groups. However, posttetanic potentiation observed after 100-, 500-, and 1000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
3
5
0
Order By: Relevance
“…For example, in mouse lumbrical muscles, isometric twitch potentiation in the absence of RLC phosphorylation has been associated with stimulation-induced elevations in resting myoplasmic Ca 2+ levels . Although this effect was relatively small and dissipated rapidly (≤20 s at 37°C), this mechanism may provide an explanation for the potentiation observed in the present study as well as by others (Macintosh et al, 2008a;Rassier et al, 1999) in the absence of RLC phosphorylation. In the current experiments, the stimulation protocol did not commence until ∼15 s after the PS, perhaps minimizing the ability of this mechanism to contribute.…”
Section: Comparison With Relevant Literaturesupporting
confidence: 78%
“…For example, in mouse lumbrical muscles, isometric twitch potentiation in the absence of RLC phosphorylation has been associated with stimulation-induced elevations in resting myoplasmic Ca 2+ levels . Although this effect was relatively small and dissipated rapidly (≤20 s at 37°C), this mechanism may provide an explanation for the potentiation observed in the present study as well as by others (Macintosh et al, 2008a;Rassier et al, 1999) in the absence of RLC phosphorylation. In the current experiments, the stimulation protocol did not commence until ∼15 s after the PS, perhaps minimizing the ability of this mechanism to contribute.…”
Section: Comparison With Relevant Literaturesupporting
confidence: 78%
“…3. This glutathionylation mechanism causing increased Ca 2+ sensitivity in fast‐twitch fibres may play a role in post‐activation potentiation and counteract the decline in isometric and dynamic performance during fatiguing exercise (Rassier & Macintosh, 2000; MacIntosh et al 2008).…”
Section: Mechanisms By Which Ros Affect Myofibrillar Force Productionmentioning
confidence: 99%
“…The overall effect depends on the balance between glutathionylation, oxidation and reversal of oxidation by cytoplasmic GSH, and will change over time particularly if levels of reduced GSH decline. J Physiol 589.9 play a role in post-activation potentiation and counteract the decline in isometric and dynamic performance during fatiguing exercise (Rassier & Macintosh, 2000;MacIntosh et al 2008).…”
Section: Figure 2 Submaximal Force Shows a Redox Maximum And Decreasmentioning
confidence: 99%
“…For example, extensor digitorum longus (EDL) muscles devoid of skeletal myosin light chain kinase, the enzyme responsible for phosphorylating the RLC, exhibit SP in the absence of RLC phosphate incorporation (Zhi et al, 2005; Gittings et al, 2011). Moreover, denervated rat gastrocnemius muscles displaying reduced levels of RLC phosphorylation retain SP (Rassier et al, 1999; MacIntosh et al, 2008). Although an alternative mechanism has not definitively been identified, our recent work has shown that posttetanic potentiation (PTP) of the mouse lumbrical, a muscle without detectable RLC phosphorylation, is associated with elevations in cytosolic Ca 2+ immediately before the onset of an intracellular Ca 2+ transient (ICT), such that baseline Ca 2+ is higher at the onset of potentiated contractions than unpotentiated contractions (Smith et al, 2013).…”
Section: Introductionmentioning
confidence: 99%